Determination of Heavy Metals in Black Sea Whiting Fish (Merlangius merlangus, Linnaeus, 1758) Species - Baki, Oylum Gokkurt; Baki, Birol (Environmental Management and Sustainable Development, 2022)
<p class="emsd-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The Black Sea is surrounded by numerous industrial and agricultural areas. Therefore, many land-based pollutants are released into the Black Sea. Discharge of industrial and agricultural untreated wastewater to the Black Sea from a single source or scattered sources has been reported. <p class="emsd-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The current study aimed to determine the concentration values of some heavy metals in the tissues of whiting fish (Merlangius merlangus, Linnaeus, 1758), one of the economical demersal species of the Black Sea. Accordingly, the accumulation concentrations of heavy metals including manganese (Mn), cobalt (Co), copper (Cu), zinc (Zn), and iron (Fe) were investigated in muscle tissue, gill, gonad, liver, and other visceral organs (except liver) in whiting fish samples. <p class="emsd-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Heavy metal concentrations determined in the muscle tissue, which are particularly important for human consumption and health were sorted as Fe>Zn>Cu>Co>Mn and the concentration values of metals were 82.84±7.11; 50.45±12.24; <0.818; <0.479; <0.413 µg.kg-1, respectively. Zn had the highest concentration in gonad tissues whereas the highest concentration determined in the liver, visceral organs, and gills was Fe. As a result of the comparison of heavy metal results obtained in the muscle tissues with the relevant standards (FAO, 2010 and FAO/WHO, 2004), it was found that they were below the risky limit values for human consumption.